(untitled) (LEGAL DIALOGICA, 2025)
This study aims to understand the legal protection of traffic accident victims, especially in the jurisdiction of the Makassar City Police and to understand the legal efforts that have been made by the Makassar City Police Unit, especially the Makassar City Police Traffic Unit in an effort to improve protection for traffic accident victims. The research method used in this study is the empirical legal research method. This research was conducted at the Makassar City Police Traffic Unit. The research data includes primary and secondary sources collected through interviews and documentation techniques. The results of the study revealed that the Makassar City Police plays an important role in handling accidents by helping victims obtain compensation, ensuring that victims’ rights are fulfilled, and supporting the applicable legal process. Accident prevention and legal protection efforts must continue to be strengthened to create road safety. In addition, the Makassar City Police Traffic Unit carries out preventive and repressive efforts, including traffic education, legal enforcement, and socialization. Although there have been efforts, accident handling has not been optimal, so innovations such as electronic systems, training, and cross-agency cooperation continue to be developed to increase the effectiveness of handling. The recommendation given by the author is for the police to continue to socialize the importance of orderly driving on the highway in order to minimize unwanted things, if necessary, take action against violators, and continue to synergize well with insurance services in order to create safety and comfort for drivers who experience accidents, both in terms of service and in terms of providing compensation. Abstrak: Penelitian ini bertujuan untuk memahami perlindungan hukum terhadap korban kecelakaan lalu lintas khususnya di wilayah hukum Polrestabes Makassar dan Untuk memahami upaya hukum yang telah dilakukan oleh satuan kepolisian Polrestabes Makassar khususnya Satuan Lalu Lintas Polrestabes Makassar dalam upaya meningkatkan perlindungan terhadap korban kecelakaan lalu lintas. Metode penelitian yang digunakan pada penelitian ini yaitu metode penelitian hukum empiris penelitian ini dilakukan pada Satlantas Polrestabes Makassar. Adapun data penelitian yaitu mencakup sumber primer dan sekunder yang dikumpulkan melalui wawancara dan teknik dokumentasi. Hasil penelitian mengungkapkan bahwa Polrestabes Makassar berperan penting dalam penanganan kecelakaan dengan membantu korban memperoleh kompensasi, memastikan hak-hak korban terpenuhi, dan mendukung proses hukum yang berlaku. Upaya pencegahan kecelakaan dan perlindungan hukum harus terus diperkuat untuk menciptakan keselamatan di jalan. Selain itu Satlantas Polrestabes Makassar melakukan upaya preventif dan represif, termasuk pendidikan lalu lintas, penindakan hukum, dan sosialisasi. Meski telah ada upaya, penanganan kecelakaan belum optimal, sehingga inovasi seperti sistem elektronik, pelatihan, dan kerja sama lintas lembaga terus dikembangkan untuk meningkatkan efektivitas penanganan. Rekomendasi yang diberikan oleh penulis yaitu kepada pihak kepolisian untuk terus mengsosialiasikan pentingnya berkendara yang tertib di jalan raya agar meminimalisir hal-hal yang tidak diinginkan, kalau perlu dilakukan juga penindakan kepada pelanggar, dan tetap bersinergi baik dengan jasa asuransi demi terciptanya keamanan dan kenyamanan pengendara yang terjadi musibah kecelakaan baik dalam segi pelayanan maupun dari segi pemberian kompensasi.